Respuesta :

Answer:

what is the question write it in thecomments and ill answer

Answer:

1.) (y+1)+y=-5

2y=-6

y=-3

x+(-3)=-5

x=-2

plug in to check if it works

2.) 2(4y+10)+y=2

9y+20=2

9y=-18

y=-2

x-4(-2)=10

x+8=10

x=2

3.) -5(-y+6)+y=0

5y-30=0

5y=30

y=6

x+(6)=6

x=0

4.) 4=6-2x

-2=2x

x=-1

y=6-2(-1)

y=8

5.) 4x-(8)=4

4x=12

x=3

4(3)-y=4

12-y=4

-y=-8

y=8

6.) 3(y-4)+y=12

4y-12=12

4y=24

y=6

x=6-4

x=2

7.) 5x-2x-6=9

3x=15

x=5

5(5)-y=9

25-y=9

-y=-16

y=16

8.)3(x-6)+x=2

4x-18=2

4x=20

x=5

y-5=-6

y=-1

hope this helped :)) also make sure to plug the x and y back into both equations :))

ACCESS MORE